Delayed Intrinsicoid Deflection of the QRS Complex is Associated with Sudden Cardiac Arrest - Darouian, Navid (Heart Rhythm, 2015)
BACKGROUND: Prolongation of initial ventricular depolarization on the 12-lead ECG, or delayed intrinsicoid deflection (DID), can indicate left ventricular hypertrophy (LVH). The possibility that this marker could convey distinct risk of sudden cardiac arrest (SCA) has not been evaluated. OBJECTIVE: To evaluate the association of DID and SCA in the community. METHODS: In the ongoing prospective, population-based Oregon Sudden Unexpected Death Study (Oregon SUDS, catchment area approx. 1 million), SCA cases were compared to geographic controls with no SCA. Archived ECGs (closest and unrelated to SCA event for cases) were evaluated for the presence of DID defined as ≥0.05 seconds in leads V(5) or V(6). LV mass and function were evaluated from archived echocardiograms. RESULTS: SCA cases (n=272, 68.7±14.6 years, 63.6% male) as compared to controls (n=351, 67.6±11.4 years, 63.3% male) were more likely to have DID on ECG (28.3% vs 17.1%, p=0.001). DID was associated with increased SCA odds (OR 1.92; 95% CI 1.31-2.81; p=0.001), but showed poor correlation with LV mass and echocardiographic LVH (kappa 0.13). In multivariate analysis adjusted for clinical and ECG markers, reduced LV ejection fraction and echocardiographic LVH, DID remained an independent predictor of SCA (OR 1.82; 95% CI 1.12-2.97; p=0.016). Additionally, in a sensitivity analysis restricted to narrow QRS, DID and ECG LVH by voltage were each independently associated with SCA risk. CONCLUSION: DID was associated with increased SCA risk independent of echocardiographic LVH, ECG LVH and reduced LV ejection fraction, potentially reflecting unique electrical remodeling that warrants further investigation.